2015
DOI: 10.1071/ah13205
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and views of a brokerage model for primary care for Aboriginal people

Abstract: Objective A mixed methods study was conducted to determine the views of Aboriginal people on their experiences of a brokerage model for access to community-based health services in an urban setting. Methods A broad range of approaches, using surveys, semi-structured interviews and community forums with Aboriginal people were used to find out people's views and experiences of using the brokerage service. Results Of the 1304 people invited to participate, only 127 people provided feedback on the brokerage servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 6 publications
(4 reference statements)
0
9
0
Order By: Relevance
“… Program evaluation Underserved African American women in Georgia. Mammogram uptake Weak (3) and thick (4) Dennis 2015 [ 17 ] Australia To explore the views of Aboriginal people on their experiences of a brokerage model for access to community-based mainstream health services in an urban setting in New South Wales. Mixed methods Aboriginal people in South West Sydney Improvement in access to health care, satisfaction with service Moderate (4) and thin (2) Findley 2011 [ 32 ] United States To describe community-based care coordination programs for childhood asthma and operational statistics at five different sites Program evaluation Low income and ethnically diverse.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Program evaluation Underserved African American women in Georgia. Mammogram uptake Weak (3) and thick (4) Dennis 2015 [ 17 ] Australia To explore the views of Aboriginal people on their experiences of a brokerage model for access to community-based mainstream health services in an urban setting in New South Wales. Mixed methods Aboriginal people in South West Sydney Improvement in access to health care, satisfaction with service Moderate (4) and thin (2) Findley 2011 [ 32 ] United States To describe community-based care coordination programs for childhood asthma and operational statistics at five different sites Program evaluation Low income and ethnically diverse.…”
Section: Resultsmentioning
confidence: 99%
“…While linkage to primary care was not necessarily the primary outcome of all the included studies, all of the studies did involve either a directly quantifiable measure of the extent to which participants were linked to primary care [ 32 35 ] or an indirect measure of linkage to care such as changes in screening behaviour or referrals to care [ 17 , 30 , 31 , 36 39 ]. Most of these measures were assessed using follow-up surveys or questionnaires.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these studies were consistent with the transformative paradigm as they sought to improve the social world for Aboriginal and Torres Strait Islander peoples through health service evaluation, 131,146,153,155,160 access to health services, 156,158 or evaluation of an intervention. 159 Other studies used mixed methods to explore social phenomena likely to be priorities for Aboriginal and Torres Strait Islander peoples including smoking cessation, 154 teenage pregnancy, 161 and cardiovascular chronic disease management in primary care.…”
Section: Mixed Methods Research Involving Aboriginal and Torres Straimentioning
confidence: 94%
“…4 Despite these limitations, a brief or rapid review involving one relevant database over a recent five year period provides useful information on the quantity of research produced in a given setting which was the aim of the review by Eades et al 4 Moreover, one evaluation of four rapid reviews found that their findings, while not as extensive, did not differ greatly from four completed systematic reviews on the same topics. 101 Cross-sectional design Yes a Gardner et al 2015 102 Cross-sectional design No Lalla et al 2015 103 Cross-sectional design Yes Radford et al 2015 104 Cross-sectional design Yes Hopkins et al 2015 105 Cross-sectional design No Arjunan et al 2015 106 Cross-sectional design No Katzenellenbogen et al 2015 107 Cross-sectional design No Pearce et al 2015 108 Cross-sectional design No Spurling et al 2014 109 Cross-sectional design Yes a Scott et al 2014 110 Cross-sectional design No Timms et al 2014 111 Cross-sectional design No Chung et al 2014 112 Cross-sectional design Yes Askew et al 2013 113 Cross-sectional design Yes a Lopez et al 2014 114 Cross 141 Qualitative Yes 153 Mixed methods Yes Gould et al 2015 154 Mixed methods No Jersky et al 2015 155 Mixed methods No Dennis et al 2015 156 Mixed methods No Govil et al 2014 157 Mixed methods Yes Thomas et al 2013 158 Mixed methods No Canuto et al 2013 159 Mixed methods No Homer et al 2012 160 Mixed methods No Larkins et al 2011 161 Mixed methods No Harris et al 2014 162 Cohort study No McDonald et al 2014 163 Cohort study No Jamieson et al 2013 164 Cohort study No Knight et al 2013 165 Cohort study No Webster et al 2013 166 Cohort study No Davis et al 2012 167 Cohort study No Robinson et al 2012 …”
Section: Sparse Research In Urban Populationsmentioning
confidence: 99%